Pengaruh Motivasi dan Pengembangan Karir terhadap Kinerja Karyawan Mc. Donald - Aprili Fajarin; Mella Yuita; Khamo Waruwu (Universitas 45 Surabaya, 2025)
The purpose of this research is to determine the influence of motivation and career development on employee performance at Mc.Donald. This research was carried out at Mc.Donald with a population and sample of 38 employees. This research instrument is a questionnaire with a Likert scale model. Requirements tests are carried out to test normality. The data analysis technique used is the Multiple Regression technique at a significance level of a = 0.05. The results of this research show that Motivation (X1) has a significant and influential effect on the performance of Mc.Donald Employees. The calculated t is greater than the t table (2.291 ˃ 1.688) with a significant value of 0.000. Meanwhile, Career Development (X2) has a significant and influential effect on the performance of Mc.Donald employees with a calculated t value greater than the t table (2.291 ˃ 1.688) with a significant value of 0.0001. Based on the SPSS output, it is known that the R squared value is 0.640, meaning that the variance in the Performance variable can be explained by the Motivation and Career Development variables of 64.0 percent, while the rest is explained by other variables not included in this model. In another sense, there are still other independent variables that influence employee performance.